Kedudukan Transfer Pemain Dalam Sepak Bola: Suatu Kajian Perspektif Hukum Islam - Fitri, Winda; Firdausa, Alif (Jurnal Komunikasi Hukum, 2021)
Currently football has become an industry that includes all forms of business activities in it. Including the matter of buying and selling players in football or better known as transfers. This research aims to find out how Islamic law reviews the position of the transfer of football players in Islam. Packaged in the form of articles that are normative legal research using secondary data types, namely data obtained from literature. The law of the transfer of football players in Islam is permissible if it does not violate the existing provisions of Islamic Law. Transfer in football is a lease (ijarah) of services, although it is often referred to as buying and selling. Allah swt justifies buying and selling and haram usury, by buying and selling what is meant is buying and selling that is not against the Islamic law.